Digital Marketing Training to Increase Business Competitiveness for Village-Owned Enterprises (BUMDes) in South Buton Regency - Herman Lawelai; Ansar Suherman; Anwar Sadat; Andy Arya Maulana Wijaya; Lia Hanifa (Society : Jurnal Pengabdian Masyarakat, 2023)
Since the widespread usage of the Internet, digital marketing has developed at an exponential rate. This level of use is driven by the availability of cell phones at low costs. However, the use of digital marketing by businesspeople, such as village-owned firms, is not generally acknowledged (BUMDes). Most BUMDes in South Buton Regency believe that digital marketing is a location for transactions to take place, which is far from the truth because digital marketing is the use of all resources on the Internet to deliver information about BUMDes' goods. BUMDes' resources include not just marketing websites but also social media platforms controlled by BUMDes. Social media utilized for digital marketing relies not just on social media created specifically for BUMDes but also on social media held by BUMDes workers. As a result of the increased reach of product promotion, product sales from BUMDes in South Buton Regency grow.